Penggunaan Agen Hayati (Beauveria bassiana) dalam Pengendalian Hama Thirathaba mundella L. pada Tanaman Kelapa Sawit - Muhammad Hanafi; Ryan Chandra Wijaya; Najibar Akmal; Irna Syofia (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2019)
This study aims to reduce the use of chemical pesticides in controlling the pest Tirathaba mundella by using biological agent Beauveria bassiana on oil palm plants. The making of Beauveria bassiana fungi isolates was carried out at the Laboratory of Plantations and Protection of Medan Plantations, and PT Cisadane Sawit Raya as the place for the research. The study used nonfactorial randomized block design (RAK) using a trial object of 21 samples of oil palm plants which were divided into 7 treatments and 3 replications, where D0 (control) was given aquadest, D1 was treated with B.bassiana suspension at a dose of 10 gr/m , D2 was treated with B.assiana suspension at a dose of 20 gr/ml, D3 was treated with B. bassiana suspension at a dose of 30 gr/ml, D4 was treated with B. bassiana suspension at a dose of 40 gr/ml, D5 was treated with B. bassiana suspension with a dose of 50 gr/ml, D6 was treated with B. bassiana suspension at a dose of 60gr/ml. Pests experienced total death on day 5 after application in treatment D5 and D6. The percentage analysis of mortality showed that on day 5 caused a very significant effect with 100% death time occurring in all oil palm bunches samples after ≥ 5 HSA.